A Case Study for Evaluating E-Commerce Websites Using Integrated Fuzzy AHP and Fuzzy TOPSIS - (:unkn) unknown (Springer Science and Business Media Deutschland GmbH, 2022)
Consumers’ lives and shopping habits have been greatly affected by uncertainties arisen from the COVID-19 pandemic and economic recession, leading to rapidly changing consumption habits and expectations. Thus, service/product providers were forced to adapt to the digital marketing trends to prevent customer churn and maintain customer loyalty. Since the digital transformation of companies going from offline to online marketing has increased competitiveness ever than before, it has become vital for companies to evaluate their service quality as well as customer satisfaction. This study aims to prioritize significant criteria of service quality and evaluate different alternatives as business-to-customer (B2C) websites with respect to those criteria using integrated Fuzzy AHP and Fuzzy TOPSIS. In this regard, four experts’ opinions are taken into account while assessing eight predetermined quality criteria and evaluating the importance weights of each. Afterward, four B2C e-commerce websites are ranked according to the predetermined eight criteria. The results obtained from this study can act as a guideline for existing e-commerce websites to assess their competitive abilities to minimize customer churn. Moreover, this study can shed light on potential companies and decision-makers that plan to consider e-commerce trends for their strategic plans. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Customer satisfaction; Digital marketing; E-commerce; Fuzziness; Multi-criteria decision-making; Service quality